Itch/β-arrestin2-dependent non-proteolytic ubiquitylation of SuFu controls Hedgehog signalling and medulloblastoma tumorigenesis - Paola Infante (Nature Portfolio, 2018)
SuFu is a tumour suppressor in medulloblastoma and regulates Gli proteins in the Sonic Hedgehog pathway; however, the molecular mechanisms behind this regulation are unclear. Here, the authors show that the Itch/β-arrestin2 complex binds and ubiquitylates SuFu, facilitating the interaction with Gli3 and its conversion into the repressive form, thus counteracting medulloblastoma formation.